reasons for the slow litigation in civil lawsuit in light of the provisions of the civil pleadings lawLecturer - Hamel Al-Ajili, Dr. Lifta (The college of law and political science journal, 2023)
The right to litigation is guaranteed constitutionally and legally, and everyperson has the right to contact the judicature to obtain the right he claims accordingto well-known litigation procedures. He is supposed to obtain that in an appropriatetime, with easy procedures, and at a low cost.However, this is not always easy, as the lawsuit procedures may take a longtime to have the right holder pay to compromise in an effort for conciliation orarbitration in order not to extend the time to lose it all, or to gain it after a hard effortwhose fruits are not equal to what he spent on it.7KHFRQÁLFWEHWZHHQWKHRSSRQHQWVHQGVLQDOOFDVHVEXWWKHUHLVDGLIIHUHQFHbetween a solution that comes at the right time, and one who runs out of patiencewaiting for that , and it is not fair to reach the truth with great effort and expenses,for that is closer to injustice than it is to justice.If the judicature is keen on enforcing the law and protecting the rights of thelitigants, it must strive to reduce the obstacles to resolving the case, and makethe right available to its owner in the fastest way and at the lowest cost, and if